An energy-efficient operation system for a natural gas liquefaction process: Development and application to a 100 ton-per-day plant. (2nd February 2017) - Won, Wangyun; Lee, Kwang Soon
Highlights: A novel energy-thrifty operation system for a natural gas liquefaction process. Combined self-optimization control and real-time steady-state optimization. New comprehensive procedure for the accurate evaluation of energy loss. Performance validation in a numerical 100 ton-per-day LNG plant. Abstract: Production of liquefied natural gas (LNG) is a highly energy-intensive process. The required liquefaction temperature is approximately −160 °C at atmospheric pressure. In this study, we propose a two-level energy-efficient operation system for an LNG process, which consists of real-time steady-state optimization (RTSSO) and real-time control subsystems. The RTSSO follows the typical design to minimize set point energy losses. In contrast, the real-time control subsystem was configured to incorporate the concept of self-optimizing control, which minimizes both implementation energy losses and set point energy losses. Special attention was given to the loss of the evaluation step so that the implementation energy loss is accurately estimated; thus, the designed system can be seamlessly applied to the actual process with guaranteed optimal energy efficiency. The performance of the proposed system was validated in a simulated LNG plant that precisely replicated an actual plant that produces 100 tons of LNG per day.